Multicentric Castleman’s Disease in a 21 Years Old Female : A Rare But Important Condition - Chowdhury, Shahed Ahmad; Reshma, Samira Taufiq; Islam, Shanjana (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2017)
Castleman’s disease, also known as angiofollicular lymph node hyperplasia, is a rare disease with two known expansion types, unicentric and multicentric, which plays a major role in determining therapy. The rare multicentric type is a lymphoproliferative disorder of unknown etiology and is characterized by various clinical manifestations and multiple organ involvement. This disease runs a more aggressive course and a poor prognosis. Optimal therapies have not been well established till now. We here report a case of rare Multicentric Castleman's Disease (MCD) in a 21yrs old female. She presented with slowly enlarging lymph nodes in cervical and inguinal regions which lead to a histological diagnosis of this rare condition. Its clinical features, types, relevant investigations and current treatment modalities are discussed. Though rare, early suspicion of this condition may relieve the suffering, avoid unnecessary investigations, give opportunity to choose treatment options and can save lives. Chatt Maa Shi Hosp Med Coll J; Vol.16 (1); Jan 2017; Page 57-59